Managing the duck curve: Energy culture and participation in local energy management programs in the United States. (September 2021) - Krietemeyer, Bess; Dedrick, Jason; Sabaghian, Ehsan; Rakha, Tarek
Abstract: Local energy management programs have the potential to flatten the so-called "duck curve" and enable greater use of renewables by engaging residents to work toward shared sustainability goals. However, there are challenges with managing energy behavior to achieve desired outcomes. This study uses the Energy Cultures framework to examine motivations for participating in a local energy program. It extends the Energy Cultures framework by demonstrating its applicability to the analysis and co-design of local energy management programs, with a particular focus on community-level engagement. The research also identifies the types of information most useful in managing energy behavior. The study site is the Mueller community in Austin, Texas, U.S.A., which has high levels of solar generation and a resulting duck curve that can be addressed by local energy management. A mixed-methods approach was utilized, with qualitative data collection through stakeholder interviews and a community workshop, followed by quantitative data collected in a survey of residents. Results show a strong interest in the proposed energy program, with residents motivated by environmental, societal, and financial benefits. Individual and social norms drove favorable responses while material culture and practices did not. Valuable types of information feedback included energy usage recommendations and renewable energy use at the individual and community level. The findings demonstrate that community engagement, energy feedback, and energy culture are interdependent and that analyzing the energy culture of a community in a co-design process can help prioritize criteria for developing energy programs and tools that strengthen and sustain community engagement.